Complications of motility peg placement for porous hydroxyapatite orbital implants. Issue 4 (1st April 2002) - Lin, C-J; Liao, S-L; Jou, J-R; Kao, S C S; Hou, P-K; Chen, M-S
Abstract : Aim: To evaluate the complications associated with pegging of porous hydroxyapatite orbital implants. Methods: Complications associated with pegging were retrospectively reviewed from the charts of 100 of 133 patients with hydroxyapatite implantation from 1993 to 2000. Results: 48 (48%) of the 100 hydroxyapatite implanted patients who had undergone pegging were found to have problems with their pegs, including discharge (45.8%), peg falling out (20.8%), pyogenic granulomas (16.7%), popping peg (14.6%), hydroxyapatite visible around peg hole (8.3%), part of peg shaft visible (6.2%), peg drilled off centre (6.2%), peg drilled at an angle (4.2%), and excess movement of peg (4.2%). The standard peg fell out statistically more often than the peg and sleeve system (Yates's corrected χ 2, p=0.038). There was a trend towards complications of the peg with use of a standard peg (versus sleeved peg) (p=0.226). Conclusions: There are several potential complications of pegging. Most complications are minor and can be managed successfully.